Successful management of fipronil toxicosis in two pet rabbits - Dario d’Ovidio; Stefano Cortellini (Open Veterinary Journal, 2022)
Background: Antiparasitic drug toxicosis is commonly described in dogs and cats, but reports on the management of antiparasitic drug toxicities in pet rabbits are scarce. Here, we describe the successful clinical management of two pet rabbits with fipronil toxicosis. Cases Description: The first case (case 1) was a 5-month-old, intact female, rabbit presented with acute onset of seizures, obtunded mentation and in lateral recumbency, while the second rabbit (case 2) was a 1-year-old, intact male presented for anorexia and lethargy. In both cases the owners reported to have administered a 0.5 ml fipronil vial topically on the skin as an antiparasitic drug between 4-6 hours prior presentation. Complete blood count and serum biochemistry were unremarkable and both rabbits tested negative on Encephalitozoon cuniculi serology. Both animals were decontaminated by bathing with tepid water and dishwashing soap. The rabbit with seizures received on admission intravenous midazolam. In both cases overnight hospitalization, intravenous isotonic crystalloid fluids as well as assisted-feeding by oral syringe was provided until voluntary feeding was resumed. Both rabbits rapidly improved approximately 12 hours of initiating supportive care. Complete resolution of clinical signs and return of normal appetite and defecation occurred within 24 hours of hospitalization in both animals. No recurrence of neurological signs was reported in the rabbit presented with seizures on a follow-up period of one month. Conclusion: The outcome of these cases suggests that supportive treatment of fipronil toxicity in pet rabbits can be successful if administered promptly.